Penerapan Prinsip Good Governance Pejabat Daerah Dalam Proses Perizinan - Pratama, Satrya Surya; Januri, Januri; Rusjana, Muhamad; Yusnandi, Yudi; Kartadinata, Andriansyah (Universitas Sang Bumi Ruwa Jurai, 2025)
Good Governance is a concept that has evolved in line with demands for bureaucratic reform in Indonesia. This article aims to examine in more depth the authority of regional officials regarding licensing and how licensing can be managed as a concrete manifestation of the implementation of Good Governance principles. This research uses a normative juridical approach, namely by reviewing/analyzing secondary data in the form of legal materials, particularly primary and secondary legal materials. In the context of implementing Good Governance, licensing management is not merely an administrative task but also an instrument for creating a government that is transparent, accountable, participatory, and responsive to public needs. However, challenges in licensing management remain a major obstacle. Complicated bureaucracy, corrupt practices, a lack of transparency, and minimal public participation often hamper the effectiveness of the licensing process